Powder coating composition
Patent Information
- Application Number
- CN202580020821.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-18
- Filing Date
- 2025-03-12
- Publication Date
- 2026-10-16
AI Technical Summary
因此,通常在使用之前或使用过程中将它们筛除,这导致产品利用率降低
[0088] The advantage of this invention is that it can achieve high gloss and DOI, especially at relatively low film thicknesses. In polyester-based powder coatings, relatively thick coatings are typically required to obtain sufficient and uniform gloss characteristics, for example, when the cured film thickness is greater than 50 µm.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a powder coating composition comprising dry-mix components. The invention also relates to a substrate coated with the powder coating composition and a method for coating the substrate with the powder coating composition. Background Technology
[0002] Powder coating compositions are solid compositions that typically contain a solid film-forming (base) polymer or a mixture of different solid film-forming polymers. These compositions may also contain other components such as pigments, extenders, and one or more functional additives such as plasticizers, stabilizers, degassing agents, and flow aids. The film-forming polymer is typically a thermosetting polymer that cures upon heating, usually in the presence of a crosslinking agent that can itself be a polymer. These polymers typically have a glass transition temperature (Tg), softening point, or melting point above 30°C.
[0003] The manufacture of powder coating compositions traditionally involves melt mixing of the composition's components. Melt mixing involves high-speed, high-intensity mixing of dry ingredients in a continuous compounding mill such as a single-screw or twin-screw extruder, followed by heating the mixture to a temperature above the softening temperature of the uncured polymer but below its curing temperature, thereby forming a molten mixture. The extruded molten mixture is rolled into sheet shape, cooled to solidify, broken into flakes, and subsequently pulverized into fine powder. The powder is typically then subjected to a series of particle size classification and separation operations, such as grinding, grading, sieving, screening, cyclone separation, sieving, and filtration.
[0004] The resulting powder coating composition is then applied to a substrate, heated to melt and fuse the particles, and the coating is cured. The powder coating composition can be applied via a fluidized bed process (in which the substrate is preheated and immersed in a fluidized bed of powder, causing the powder to fuse and adhere to the substrate upon contact with a hot surface), a hydrostatic bed process, or an electrostatic spraying process (in which powder coating particles are electrostatically charged and guided to a grounded substrate via electrodes within a fluidized bed or via an electrostatic spray gun).
[0005] Powder coating compositions are typically formulated as so-called one-component compositions, which are prepared by melting together the base material, crosslinking, and additive components, and then extruding and grinding or pulverizing the composition to form powder coating particles with a suitable particle size. Optionally, additional powder coating additives may be dry-mixed with the extruded particles, for example, to improve flowability.
[0006] Examples of one-component powder coating compositions having dry-mix additive components are disclosed in WO 00 / 01774, WO 2021 / 245043, WO 2021 / 245044, WO 2021 / 245045 and WO 2021 / 245046.
[0007] Fine powder may be generated during the production and processing of powder coatings. During spray application, this fine powder often does not end up on the substrate but begins to accumulate in the spray booth and within the recycled powder. Therefore, it is typically screened out before or during use, resulting in reduced product utilization. Advantageously, fine powder can be used or reused to a certain extent to avoid such waste. Summary of the Invention
[0008] A specific dry-mixed silica additive has been discovered that can help improve the utilization of fine powders.
[0009] This invention provides a powder coating composition comprising a first powder coating component dry-mixed with silica, wherein: - The first powder coating component comprises a curable resin and a curing additive for curing the curable resin and has a density of 150µm or less. v 90 particle size, and - At least 95% by weight of the dry-mixed silica is porous silica with an average particle size (D[4,3]) in the range of 2-20 µm and a pore volume in the range of 0.8-3.0 mL / g, and - The amount of the dry-mixed porous silica in the powder coating composition is in the range of 0.01-0.70% by weight.
[0010] In a second aspect, the present invention provides a method for coating a substrate with the powder coating composition.
[0011] In a third aspect, the present invention provides a substrate coated with the powder coating composition. Attached Figure Description
[0012] Figure 1 To show the particle size distribution of the powder coating composition of Comparative Example 3 before spraying and after deposition on the substrate.
[0013] Figure 2 The graphs illustrate the particle size distribution of the powder coating composition of Example 3 before spraying and after deposition on the substrate.
[0014] Figure 3 To show the particle size distribution of the powder coating composition of Comparative Example 6 before spraying and after deposition on the substrate.
[0015] Figure 4 The graphs illustrate the particle size distribution of the powder coating composition of Example 8 before spraying and after deposition on the substrate.
[0016] Figure 5The graphs show the particle size distribution of the powder coating composition of Example 9 before spraying and after deposition on the substrate.
[0017] Figure 6 The graph shows the reflectance versus wavelength for the powder coating composition of Comparative Example 3 at various film thicknesses.
[0018] Figure 7 The graph shows the reflectance versus wavelength of the powder coating composition of Example 3 at various film thicknesses.
[0019] Figure 8 Showing the convex side of the bent aluminum sheet ( Figure 8 a) and concave surface ( Figure 8 Photograph b) shows the powder coating of Comparative Example 5 applied to the convex surface. The coating in these photographs is not yet cured.
[0020] Figure 9 Showing the convex side of the bent aluminum sheet ( Figure 9 a) and concave surface ( Figure 9 Photograph b) shows the powder coating of Example 5 applied to a convex surface. The coating in these photographs is not yet cured.
[0021] Figure 10 This is a photograph of a concave aluminum substrate with a flat top surface and four recessed areas of varying depths. The powder coating composition of Comparative Example 5 has been sprayed onto this substrate, with the spray applied vertically into the recessed areas. The coating in this photograph is uncured.
[0022] Figure 11 This is a photograph of a concave aluminum substrate with a flat top surface and four recessed areas of varying depths. The powder coating composition of Example 5 has been sprayed onto the substrate from directly above and applied to the recessed areas. The coating in this photograph is uncured.
[0023] Figure 12 is Figure 10 A side view photograph of the concave substrate shown.
[0024] Figure 13 is Figure 11 A side view photograph of the concave substrate shown. Detailed Implementation
[0025] [Overall Review]
[0026] Various granularities are mentioned below. D v 90 represents the particle size value when 90% of the total particles have a particle size lower than this value. (D) v 50 represents the particle size value when 50% of the total particles have a particle size lower than this value. The average particle size is the volume-based average particle size and is usually expressed as D[4,3]. In all these measurements, D represents the diameter.
[0027] Including D v 90. D v Particle size, including 50 and D[4,3] values, can be measured by laser diffraction. One approach is to use the Mie model in the implementation according to ISO 13320 (2020).
[0028] Pore properties, such as pore volume, can be conveniently measured by gas adsorption techniques, such as nitrogen adsorption. An example method is ISO 15901-2 (2022).
[0029] The number particle size distribution (based on density) for various size ranges by weight % can be calculated and determined using an electrically sensed zone method (e.g., using a Coulter counter). The appropriate method to use is ISO 13319 (2021).
[0030] The term "dry blend" is used to describe the physical mixture of the powder components in a powder coating composition. A dry blend of powder coating components differs, for example, from a co-extrusion mixture in which several components are mixed and co-extruded together (e.g., by melt extrusion), and then the extruded mixture is broken into powder particles. A dry blend also differs, for example, from binder powder particles in which one component is embedded within or bonded to the particles of another component; an example is the "bonding" of metallic effect pigment particles to particles containing a curable resin, wherein the particles containing the curable resin are heated above the glass transition temperature of the resin, brought into contact with the metallic effect pigment particles, and then cooled.
[0031] Gloss and image sharpness are commonly measured coating properties. Gloss can be measured using ASTM D523-14 (2018). Image sharpness can be measured using ASTM D5767-18 (2023).
[0032] [Powder Coating Composition]
[0033] The powder coating composition comprises a first powder coating component and optionally, one or more additional powder coating components in dry blend. Each powder coating component comprises a curable resin and a curing additive for curing the curable resin.
[0034] Each powder coating component is a powder material, wherein each powder particle contains both a curable resin and a curing additive. This type of powder coating component is sometimes referred to below as a component containing a curable resin.
[0035] The powder coating composition also comprises dry-mixed silica, wherein at least 95% by weight is porous silica having the properties further described below. The silica is in powder form.
[0036] In an embodiment, the powder coating composition may also contain a high proportion of, in particular, the first powder coating component and any additional small particles (fine powder) of the powder coating component containing a curable resin.
[0037] [First Powder Coating Component]
[0038] The powder particles of the first powder coating component can be obtained by melt mixing the constituent components in a compounding machine such as an extruder. When melt mixing is used, the powder particles of the first powder coating component contain a polymer that can be softened or melted in the compounding machine. The polymer can be the curable resin, any polymer curing additive, or both. Optionally, other powder coating components may also be included, such as pigments, extenders, or functional additives, such as melt flow agents, degassing agents, or dispersants.
[0039] Typical D of the first powder coating component v 90. Particle size is 150µm or smaller, for example, 130µm or smaller. D v 90 is typically at least 20µm, for example at least 30µm.
[0040] The first powder coating component comprises one or more curable resins. It also comprises one or more curing additives for use with the one or more curable resins. The curable resins and curing additives can be collectively referred to as a curing system.
[0041] In the implementation scheme, the amount of curable resin and curing additive in the first powder coating component is at least 40% by weight, for example 40-90% by weight, such as 50-80% by weight.
[0042] [Additional powder coating components]
[0043] In an embodiment, additional powder coating components may be present, comprising one or more curable resins and one or more curing additives for the curable resin. These are generally as described above for the first powder coating component, but differ from the first powder coating component in composition in that at least one of the curable resins or curing additives is different from the first powder coating component, and / or the relative ratio of the curable resin to the curing additive is different.
[0044] Compositional differences refer to variations in the composition of the curable resin or curing additive, or both, compared to the first powder coating component. For example, this could mean using different relative amounts of the curable resin and curing additive, or using different curable resins or curing additives. Different resins could be different types of resins (e.g., epoxy resin versus polyester resin) or resins of the same type but with different properties (e.g., in terms of molecular weight, hydroxyl value, glass transition temperature, etc.). Similarly, different curing additives could refer to different types of curing additives (e.g., β-hydroxyalkylamide versus isocyanate) or curing additives with different properties (e.g., different functional group contents).
[0045] Any additional powder coating components that may be present are dry-mixed with the first powder coating component and the dry-mixed porous silica. In one embodiment, the powder coating composition contains no more than 50% by weight, for example, no more than 40% by weight or no more than 30% by weight of such additional powder coating components. In another embodiment, no additional powder coating components are present, and the powder coating composition is a so-called "one-component" powder coating composition.
[0046] In the embodiments, the total amount of the first powder coating component and any additional powder coating components in the powder coating composition is at least 50% by weight, for example, in the range of 50-99.99% by weight, for example, in the range of 60-99.95% by weight or 60-99.90% by weight.
[0047] [Curing System]
[0048] The term "curing system" can be used to describe the combination of curable resins and curing additives within a powder coating component.
[0049] The curing additive is a compound capable of curing the curable resin, such as a curing agent, curing catalyst, free radical initiator (e.g., thermal free radical initiator or photoinitiator), accelerator, or inhibitor. In this document, the term "curing catalyst" refers to a compound that catalyzes the crosslinking reaction between the curable resin and the curing additive, or, in the case of a self-crosslinking curable resin, catalyzes a self-crosslinking reaction.
[0050] One or more curing additives may be present in the curing system of the first powder coating component and / or any additional powder coating components. The one or more curing additives for curing the curable resin preferably comprise a curing agent and / or a curing catalyst that crosslinks with the curable resin. The crosslinking curing agent may be the resin itself, such as an epoxy resin crosslinked with a carboxyl-functionalized polyester resin or a polyamine resin crosslinked with an epoxy resin. It should be understood that in the case of a curing system having a curable resin and a curing agent that is itself a resin, either of these resins can be considered as the curable resin or the curing additive.
[0051] One or more curable resins may be present in the first powder coating component and / or any additional powder coating components. Suitable curable resins include, for example, carboxyl-functional resins such as carboxyl-functional polyesters, polyester-amides, or (meth)acrylate-based resins; amine-functional resins such as polyamides or polyester-amide resins; hydroxyl-functional resins such as hydroxyl-functional polyesters; epoxy-functional resins (including glycidyl-functional resins); anhydride-functional resins; and resins with unsaturated bonds such as unsaturated polyesters.
[0052] Curing additives such as crosslinking curing agents or curing catalysts for curing this type of curable resin are well known in the art. Suitable curing additives for curing carboxyl-functionalized resins include, for example, β-hydroxyalkylamides, polyisocyanates such as triglycidyl isocyanurate, and epoxy-functionalized resins.
[0053] Curing additives suitable for curing epoxy functional resins include amines and isocyanates such as polyisocyanates.
[0054] In one embodiment, the curable resin is a carboxyl-functionalized polyester, a carboxyl-functionalized polyacrylate, a hydroxyl-functionalized polyester, or a hydroxyl-functionalized polyacrylate. In this embodiment, it is a carboxyl-functionalized or hydroxyl-functionalized polyester. Any of these can be used in combination with one or more curing additives selected from β-hydroxyalkylamides (HAAs), polyisocyanates such as triglycidyl isocyanate (TGIC), and epoxy-functionalized resins.
[0055] In another embodiment, the curable resin (or at least one of the curable resins) is an epoxy-functional resin, and the curing additive (or at least one of the curing additives) is an amine compound or an amine-functional resin.
[0056] In the implementation scheme, the curing system may suitably be an epoxy-polyester system or a polyester-HAA system. In an epoxy-polyester curing system, the curing additive may be an epoxy resin and the curable resin may be a polyester resin having crosslinkable functional groups (such as carboxyl-functionalized polyesters or hydroxyl-functionalized polyesters), wherein the epoxy resin is crosslinked with the functional groups on the polyester resin. In a polyester-HAA curing system, the curing system comprises a polyester resin and HAA.
[0057] The polyester resins that can be used include saturated carboxyl-functionalized polyester resins. In embodiments, they have an acid value in the range of 10-100 mg KOH / g, for example, in the range of 20-90 or 20-70 mg KOH / g. In embodiments, the glass transition temperature is in the range of 20-80°C, for example, in the range of 40-70°C or 55-65°C. In embodiments, the viscosity is 500-7000 mPa·s @200°C, for example, 1000-5500 or 1500-4000 mPa·s @200°C.
[0058] The epoxy resin may be a bisphenol-based epoxy resin. In embodiments, they have an epoxy equivalent (EEW) of 300-1400 g / eq, for example 400-1200 or 500-900 g / eq. In embodiments, the softening point is 60-120°C, for example 70-115°C or 80-105°C. In embodiments, their melt viscosity can be in the range of 300-30000 mPa·s @150°C, for example 600-20000, 800-10000, 1000-7000 or 1200-4000 mPa·s @150°C.
[0059] In the implementation scheme, the curing system is capable of curing at temperatures in the range of 130-240°C, for example, 140-220°C.
[0060] [Other Additives]
[0061] Separate from dry-mixed silica (discussed further below), the powder coating composition may contain one or more other additives, which may be selected from stabilizers, leveling agents, anti-settling agents, matting agents, rheology modifiers, preservatives, toughening agents, surfactants, UV light absorbers, light stabilizers, amine synergists, waxes, adhesion promoters, flow aids, gloss enhancers, fillers, pigments, flow control agents, degassing agents, and antioxidants.
[0062] Other additives may be included as part of any powder coating component containing a curable resin, for example, added before or during the melt mixing / extrusion process as described above. Additionally or alternatively, they may be bonded to any powder coating component containing a curable resin. The bonding of additive particles (e.g., pigment particles) to powder component particles containing a curable resin is known in the art and is typically achieved by heating the powder coating component under an inert atmosphere to a temperature close to but below the glass transition temperature of any curable resin in the powder coating component; while maintaining the heating temperature, adding other additives (such as solid pigments) to the heated powder coating component under stirring until the additives bond to the powder coating component particles, typically after 10-20 minutes; and cooling the powder coating composition.
[0063] Alternatively or separately, they can be dry-mixed with the powder coating components containing the curable resin and the porous silica.
[0064] The total amount of these other additives can be in the range of 0-40% by weight, for example, 0-35% by weight or 0-30% by weight. When any of these other additives are present, their minimum concentration (alone or in combination) in the powder coating composition is typically at least 0.05% by weight, for example, at least 0.1% by weight.
[0065] In the implementation scheme, the one or more other additives comprise one or more dry-mixed inorganic particulate additives. Examples include inorganic color pigments, inorganic effect pigments such as metallic effect pigments, biocidal pigments, anticorrosive pigments, extenders, opaque pigments, flow aids, conductive or antistatic pigments, infrared absorbing pigments, radiation shielding pigments, glass flakes, abrasion resistant agents, or any combination of two or more of these.
[0066] The total amount of dry-mixed inorganic particulate additives can be up to 35% by weight, for example, up to 30% by weight or up to 25% by weight.
[0067] In one embodiment, the one or more dry-mixed inorganic particulate additives include dry-mixed alumina, aluminum hydroxide, or a mixture thereof. In another embodiment, the total amount of the dry-mixed silica, alumina, and aluminum hydroxide is in the range of 0.1-1.5% by weight, for example, 0.1-1.2% by weight or 0.1-1.0% by weight.
[0068] Porous silica
[0069] The powder coating composition comprises dry-mixed silica, wherein at least 95% by weight is porous silica with an average particle size of 2-20 µm as determined by laser scattering. The content of the dry-mixed porous silica is in the range of 0.01-0.70% by weight based on the total content of the powder coating composition.
[0070] Other sources of silica may be present in the coating composition (as an additive in the dry mix or incorporated into the first or additional powder coating components).
[0071] The amount of any other dry-mixed silica in the coating composition (i.e., silica that is not porous and / or has a different average particle size) is no more than 5% by weight of the total dry-mixed silica, for example, no more than 3% by weight or no more than 1% by weight. In an embodiment, there is no other dry-mixed silica in the powder coating composition, i.e., 100% by weight of the dry-mixed silica is porous silica with an average particle size of 2-20 µm and a porosity of 0.8-3.0 mL / g.
[0072] In one embodiment, the coating composition contains no more than 5% by weight of any other silica, for example, no more than 3% by weight or no more than 1% by weight, based on all the silica present in the coating composition (e.g., the sum of all dry-mixed silica and all silica incorporated into or bonded to the first or additional powder coating component). In another embodiment, no other silica is present in the powder coating composition.
[0073] Silica refers to a material that can generally be represented by the formula SiO2. It excludes silicates such as aluminosilicates and silicates, as well as glasses and ceramics composed of oxide mixtures. In this embodiment, the porous silica has a density of 0.8 g / cm³. 3 Or even smaller, for example, in the range of 0.05-0.80 g / cm³. 3 The packing density within the range.
[0074] This porous silica is typically not fumed silica (i.e., produced by pyrolysis) because these tend to be non-porous. In embodiments, the porous silica is derived from precipitated or colloidal silica in a silicate solution (e.g., alkali metal silicates such as sodium silicate). This porous silica has a pore volume in the range of 0.8-3.0 mL / g, for example, 1.0-2.5 mL / g.
[0075] The porous silica is typically untreated or unmodified silica, but in some embodiments it may also be selected from hydrophilic surface-modified silica and hydrophobic surface-modified silica. In other embodiments, the dry-mixed silica does not contain polymer-coated silica or wax-coated silica.
[0076] Using the dry-mixed porous silica described herein helps improve the uniformity of powder coating particle deposition on substrates across a wide particle size range. It also allows for the incorporation of a greater proportion of fine powder into the deposited layer.
[0077] [powder]
[0078] Fine powder particles, especially those from powder coating components containing curable resins, are generally undesirable because (compared to larger particles) they are relatively unlikely to form part of the coating and instead tend to accumulate in recycled powder. Therefore, they must typically be removed before or during use, resulting in material waste. They can also reduce powder flowability, making it difficult to spray.
[0079] In the powder coating compositions described herein, the incorporation of fine powders in the applied coating is significantly improved. This, for example, means that less fine powder sieving is required before or during the coating application process. It also provides a method for increasing the fine powder content, for example, by incorporating fine powders of the first and / or additional powder coating components into the powder coating composition. Higher fine powder content has been found to provide particular advantages in cured coatings, such as high gloss and improved image clarity at low coating thicknesses, particularly at low film thicknesses. In an embodiment, at least 85% (based on numerical values) of the fine powders in the powder coating composition is deposited on the substrate.
[0080] Fine powder refers to particles with a particle size of 10µm or smaller.
[0081] The powder coating composition may contain 5% by weight or more of fine powder. In embodiments, this amount is based on the powder coating composition as a whole being 7% by weight or more, 10% by weight or more, or 12% by weight or more. The total amount of fine powder is generally no more than 50% by weight of the powder coating composition, for example, no more than 40% by weight or no more than 35% by weight. Example ranges include 5-50% by weight, 5-40% by weight, 5-35% by weight, 7-50% by weight, 7-40% by weight, 7-35% by weight, 10-50% by weight, 10-40% by weight, and 10-35% by weight. The fine powder content can be determined by particle number distribution.
[0082] In the implementation scheme, the percentage of fine powder deposited on the substrate after spray application is at least 85% (based on a numerical value, e.g., determined by laser diffraction) compared to the fine powder in the coating before spray application.
[0083] [Paint Application]
[0084] The substrate can be any substrate suitable for powder coating, such as metal, wood, plastic, or a substrate containing any of these materials. In this embodiment, the substrate is a metal substrate.
[0085] Prior to applying the powder coating composition, the substrate surface may be treated to remove any contaminants and / or improve the substrate's corrosion resistance. Such surface treatments are well known in the art and are commonly applied to surfaces to which the powder coating will be applied.
[0086] The powder coating composition of the present invention can be applied as a topcoat onto a first layer of powder coating composition. The first layer can be a powder coating composition different from those described herein. Thus, in one embodiment, the substrate is coated with a first layer of the first powder coating composition, followed by a second layer of the powder coating composition of the present invention.
[0087] This powder coating composition can be applied by spraying, preferably by using a corona gun.
[0088] The advantage of this invention is that it can achieve high gloss and DOI, especially at relatively low film thicknesses. In polyester-based powder coatings, relatively thick coatings are typically required to obtain sufficient and uniform gloss characteristics, for example, when the cured film thickness is greater than 50 µm.
[0089] In this application, high and uniform gloss can be achieved with a cured film thickness of 50µm or less, such as 45µm or less, 40µm or less, or even 35µm or less. The cured coating thickness in the embodiments is also at least 20µm or at least 25µm.
[0090] The cured coating can have high gloss properties. In one embodiment, the cured coating has a 60° gloss value of 85 or greater, for example, 90 or greater. In another embodiment, the 60° gloss does not exceed 200, and in other embodiments it does not exceed 150 or 100.
[0091] Another advantage is good flow and leveling properties, which can manifest as a high image sharpness value for the cured coating. In this embodiment, the image sharpness measured at 60° is at least 30, for example, at least 35. It typically does not exceed 200 and in other embodiments it does not exceed 150 or 100.
[0092] The present invention is now described by the following non-limiting embodiments and accompanying drawings.
[0093] Example
[0094] [Powder Coating Examples]
[0095] The compositions of Comparative Examples 1-5 and Examples 1-5 are shown in Table 1. The components mentioned in the upper part of Table 1 (below "Extrudate") were mixed together and melt-extruded, then pulverized into a dry powder to obtain a D0 of 50-100 µm. v 90. The extruded powder components are then dry-mixed with the additives shown in the lower half of Table 1.
[0096] Examples 6-9 are based on the extrudate portion of Example 1, but contain higher levels of fine powder, at 10.1% and 13.3% by weight respectively, and only half the amount of dry-mix additive (i.e., 0.5% by weight in total).
[0097] Comparative Examples 6-11 are also based entirely on the extrudate portion of Example 1, but with different amounts and / or types of dry blend components. The formulations of Examples 6-9 and Comparative Examples 6-11 are shown in Table 2.
[0098] Table 1—Powder Coating Compositions (wt%) [1]
[0099] [1] C.Ex. = Comparative example, Ex. = Example
[0100] [2] Carboxyl-functionalized unsaturated polyester resin
[0101] [3] Bisphenol A epoxy resin
[0102] [4] Total amount of pigments and fillers
[0103] [5] Total amount of flow aids, waxes, antioxidants, benzoin and viscosity modifiers
[0104] [6] Syloid™ C812 silica, D[4,3] average particle size 11µm, pore volume 2.0mL / g.
[0105] [7] % by weight of particles with a particle size ≤10µm (based on the entire powder coating composition)
[0106] Table 2—Formulations (parts by weight) of Examples 6-9 and Comparative Examples 6-11
[0107] [1] Extrudate of Example 1
[0108] [2] Syloid™ C812 silica, D[4,3] average particle size 11µm, pore volume 2.0mL / g.
[0109] [3] Aerosil™ R972 (non-porous) fumed silica
[0110] [4] HDK™ H3004 (non-porous) fumed hydrophobic silica
[0111] [Experiment 1—Comparison of Deposited Fine Powder]
[0112] Add 400g of powder coating to a 3L fluidized bed. Apply the powder to a fixed 15cm x 10cm aluminum plate at a set voltage of 90kV (or 70kV for Comparative Example 6 and Examples 8 and 9) using a GEMA negative corona spray gun. Deposit a total of 1-2g of powder coating onto the substrate.
[0113] Powder samples deposited on the plate were taken and particle size measurements were performed using a Mastersizer™ Coulter counter. This was compared to a sample of powder collected from the fluidized bed before spraying.
[0114] Table 3 shows the relative proportion (in terms of quantity %) of fine powder in the deposited layer compared to the uncoated material.
[0115] Table 3—Percentage of fine powder in the deposited layer (quantity %) compared to the composition before spraying
[0116] Compared to the comparative example, the deposited coating of the embodiment contains a significantly higher proportion of fine powder.
[0117] Figure 1 and 2 The graphs show the particle number in the powder coating compositions of Comparative Example 3 and Example 3 before deposition and spraying over a wider particle size range. Compared to Comparative Example 3, the particles in Example 3 are more uniformly incorporated into the powder coating across all particle size ranges.
[0118] In respectively Figure 3-5 Similar effects were observed in Comparative Example 6, as well as Examples 7 and 8. Compared to the comparative examples without porous silica, the examples exhibited more consistent deposition profiles.
[0119] [Experiment 2—Coating Integrity]
[0120] The powder coating was deposited on a plate in the same manner as described for Experiment 1 above, except that the plate used was 30 × 15 cm. The powder coating was then cured in a convection oven at 190°C for 15 minutes. Plates with variable powder weights were prepared to obtain variable coating thicknesses. The reflectance of each sample was collected and measured at the center of the plate using a Datacolour 800 instrument. The results are shown in Table 4.
[0121] Table 4—Optical Properties of Powder Coatings
[0122] D65 ΔE This indicates the degree of color change of the sample compared to the thickest powder coating. ΔL The value represents the difference between transmittance and reflectance.
[0123] These results indicate that, compared to the comparative example, this embodiment maintains its optical properties to a much greater extent at a lower thickness, as it exhibits smaller color variations and transmittance differences. This is also shown in... Figure 6 and 7 These findings highlight that, compared to Comparative Example 3, Example 3 maintains better hiding power in the visible light wavelength range (450-700 nm) at lower coating thicknesses. These results indicate that, compared to the Comparative Example, this embodiment improves coating uniformity and spread at low film thicknesses.
[0124] [Experiment 3—Glossiness and Image Sharpness]
[0125] Powder coating was applied to 15×30cm aluminum plates in a manner similar to that described in Experiment 1, and the samples were subsequently cured in a convection oven. For Comparative Examples 3 and 4, and for Examples 3 and 4, the curing conditions were 180°C for 15 minutes. For Examples 1, 6 and 8-9, and for Comparative Examples 1 and 6-11, curing was carried out at 190°C for 15 minutes.
[0126] The 60° gloss and DOI values of the cured coating were then obtained at 10 different points on the surface using a Rhopoint IQ meter. DOI measurements were recorded using the same instrument as for the gloss measurement, also taken at a 60° angle. Readings were taken at 10 different points on the surface. The average 60° gloss and DOI results are listed in Table 5.
[0127] Table 5—Gloss and DOI Measurements
[0128] [1] This powder coating has very poor flowability.
[0129] [2] The powder had extremely poor deposition efficiency and was not cured. Its properties were not determined.
[0130] The results show that at film thicknesses less than 50 µm, the examples typically exhibit both high 60° gloss values and high 60° DOI values, while the comparative examples generally have worse DOI values and, in most cases, worse gloss. The results also indicate that, compared to the comparative examples at higher film thicknesses, the examples can exhibit comparable or even improved gloss and DOI values at greater film thicknesses. Even when the values between the comparative examples and the examples are similar at comparable film thicknesses, the examples exhibit improved fine powder utilization.
[0131] [Experiment 4—Spraying Application Performance]
[0132] The powder coatings of Example 5 and Comparative Example 5 were sprayed onto the convex surface of a curved aluminum substrate. The corresponding concave surface had a depth of 50 mm. Photographs of the resulting substrates (after spraying but before curing) are shown for Comparative Example 5 and Example 5, respectively. Figure 8 and 9 ,in Figure 8 a and 9a indicate convex surface 1 and Figure 8 b and 9b show concave surface 2.
[0133] Compared to Comparative Example 5, Example 5 shows better coverage on the convex surface 1. Compared to Comparative Example 5, the coating coverage on the concave surface 2 of Example 5 shows a significant improvement, especially at the apex of the curved surface.
[0134] Figure 10 and 11 Similar test results are shown for Comparative Example 5 and Example 5, respectively, on steel substrates with grooves of various depths, wherein the spray is applied toward the concave surface of the substrate.
[0135] The substrate has a flat plate edge 3 and grooves of different depths as follows: 4=44mm, 5=20mm, 6=35mm and 7=46mm.
[0136] Figures 12 and 13 show the relationship with Figure 10 and 11 Side 8 of the same substrate shown (for Comparative Example 5 and Example 5, respectively).
[0137] The powder coating of Example 5 exhibited a more uniform distribution in every case, particularly in the recessed areas. Example 5 also showed better wrap-around performance, providing better coverage on surfaces 8 not directly aligned with the sprayed coating. Example 5 also demonstrated improved coverage uniformity on the edges 3 of the flat sheet and in the recessed areas 4-7.
[0138] In contrast, Comparative Example 5 not only exhibits worse “wrapping” performance on the side 8, but also shows significantly less uniform coverage overall, with a relatively thicker coating at the flat edge 3 of the concave substrate and relatively poorer penetration and coverage uniformity in the recessed areas 4-7.
[0139] After curing at 200°C for 15 minutes, poor coating integrity was observed in the recessed region 2 of the curved aluminum substrate, as well as in regions 4 and 7 of the concave substrate, for Comparative Example 5. In contrast, good coating integrity was observed in all regions of both the curved and concave substrates for Example 5.
Claims
1. A sprayable powder coating composition comprising a first powder coating component dry-mixed with silica, wherein the first powder coating component comprises a curable resin and a curing additive for curing the curable resin and has a density of 150 µm or less. v 90 particle size At least 95% by weight of the dry-mixed silica is porous silica with an average particle size of D[4,3] in the range of 2-20µm and a pore volume in the range of 0.8-3.0mL / g, and the amount of the dry-mixed porous silica in the powder coating composition is in the range of 0.01-0.70% by weight.
2. The powder coating composition of claim 1, comprising at least 5% by weight particles with a particle size of 10µm or smaller.
3. The powder coating composition according to claim 1 or 2, wherein at least 95% by weight of all silica in the coating composition is dry-mixed porous silica with an average particle size of 2-20 µm.
4. The powder coating composition according to any one of claims 1-3, wherein the curable resin is selected from carboxyl-functional polyesters, carboxyl-functional polyacrylates, hydroxyl-functional polyesters and hydroxyl-functional polyacrylates, and the curing additive is selected from β-hydroxyalkylamides, polyisocyanates and epoxy functional resins.
5. The powder coating composition of any one of claims 1-4, wherein there are one or more additional powder coating components, each comprising a curable resin and a curing additive for curing the curable resin, wherein the curable resin and / or curing additive in each additional powder coating component is different from the curable resin and / or curing additive in the first powder coating component, and / or the relative ratio of the curable resin to the curing additive in each additional powder coating component is different from the relative ratio in the first powder coating component.
6. The powder coating composition according to any one of claims 1-5, wherein the total amount of the first powder coating component and any additional powder coating components in the powder coating composition is at least 50% by weight.
7. The powder coating composition according to any one of claims 1-6, further comprising one or more other dry-mixed additives.
8. The powder coating composition of claim 7, wherein the other dry-mixed additive comprises a dry-mixed inorganic particulate additive, the amount of which in the powder coating composition is up to 35% by weight.
9. The powder coating composition according to any one of claims 1-8, wherein one or more of the following properties are applicable: (i) The porous silica has a density of 0.8 g / cm³. 3 Or even lower stacking density; (ii) The amount of particles with a particle size of 10 µm or smaller is at least 7% by weight, at least 10% by weight, or at least 12% by weight; (iii) The total amount of dry-mixed silica, alumina and aluminum hydroxide is in the range of 0.1-1.5% by weight.
10. The powder coating composition according to any one of claims 1-9, wherein the dry-mixed silica does not contain fumed silica.
11. A substrate coated with, optionally after curing, a powder coating composition according to any one of claims 1-10.
12. The substrate of claim 11, wherein the powder coating composition is cured and the cured powder coating composition has one or more of the following properties: (i) Film thickness of 50 µm or less; (ii) A gloss value of 85 or greater at 60°; (iii) 30 or greater 60° image sharpness value.
13. A method of coating a substrate, comprising spraying a powder coating composition according to any one of claims 1-10 onto the surface of the substrate and curing the powder coating composition.
14. The method of claim 13, wherein at least 85% of the particles (based on numerical values) of the powder coating composition having a particle size of 10 µm or smaller are deposited on the substrate.
15. The method of claim 13 or 14, wherein the cured powder coating composition has one or more of the following properties: (i) Film thickness of 50 µm or less; (ii) A gloss value of 85 or greater at 60°; (iii) 30 or greater 60° image sharpness value.
Citation Information
Patent Citations
Powder coating compositions
WO2000001774A1
Powder coating composition and substrate coated with such powder coating composition
WO2021245043A1
One-component powder coating composition and substrate coated with such powder coating composition
WO2021245044A1
One-component powder coating composition and substrate coated with such powder coating composition
WO2021245045A1
One-component powder coating composition and substrate coated with such powder coating composition
WO2021245046A1